Electronic spin-spin decoherence contribution in molecular qubits by quantum unitary spin dynamics - Sanvito, Stefano; Lunghi, Alessandro (Elsevier BV, 2019)
The realisation of quantum computers based on molecular electronic spins requires the design of qubits with very long coherence times, . Dephasing can proceed over several different microscopic pathways, active at the same time and in different regimes. This makes the rationalisation of the dephasing process not straightforward. Here we present a computational methodology able to address spin decoherence processes for a general ensemble of spins. The method consists in the propagation of the unitary quantum spin dynamics on a reduced Hilbert space. Then we study the dependence of spin dephasing over the magnetic dilution for a crystal of Vanadyl-based molecular qubits. Our results show the importance of long-range electronic spin-spin interactions and their effect on the shape of the spin-echo signal.
PUBLISHED
Keywords: Dephasing; Quantum computers; Molecular electronic spins